Scanning electron microscope investigation on the process of healing of skin wounds in Cirrhinus mrigala. Issue 11 (11th August 2017) - Verma, Neeraj; Kumari, Usha; Mittal, Swati; Mittal, Ajay Kumar
Abstract: Present scanning electron microscope study, reports healing of excised skin wounds in Cirrhinus mrigala . Healing process of wounds, inflicted on head skin, using biopsy punch was observed at intervals—0 hour (h), 1, 2, 4, 6, 12 h, 1 day (d) 2 and 4 d. Accumulation of mucus in wound region within 1h after infliction of wound has been considered an immediate measure to provide protection to injured skin from microbial invasion and other external environmental hazards. On infliction of wound, mobilization of epithelial cells at wound edge is associated with disturbance of coaptive relationship of epithelial cells till original coaptive stability is reached. At 6–12 h appearance of epidermal ridge in region of contact of migrating fronts is due to piling up of epithelial cells. This is associated with cessation of migration of epithelial cells and their simultaneous continual arrival in the region. Speedy epithelialization of skin wounds in C. mrigala like in other fishes, compared to that of mammals and other higher vertebrates, is possibly facilitated owing to surrounding wet external environment. Microridges in initial stages of wound healing appear fragmented without particular orientation. Further, epithelial cells in epithelium in wound region and in region adjacent to wound elongate. These changes are associated with the stretching of epithelial cells indicating their streaming and migration, toward wound. Presence of superficial neuromasts, smallest functional units of lateral line system, a hydrodynamic sensory system, has been associated with important functional significance in fish. Abstract : Healing of skin wounds in Cirrhinus mrigala was studied using scanning electron microscopy. Covering of wound by mucus, rapid epithelialization, and changes in pattern of microridges on the surface of epithelial cells during healing are significant.